When Ghosts Hovered: Community and Crisis in a Company Town, Britannia Beach, British Columbia, 1957-1965 - Rollwagen, Katharine (Urban History Review / Revue d'histoire urbaine, 2007)
This article compares two shutdowns in the copper-mining town of Britannia Beach, British Columbia. It explores the extent to which community was a “sufficiently empowering myth” to unite residents against their employers' respective closure attempts. During a 1958 shutdown triggered by plummeting copper prices, divisive notions of community, coupled with loyalty to long-time employer Britannia Mining and Smelting Company, produced despair rather than resistance among residents. Most left Britannia to find other work, and few returned when the mine reopened ten months later. Conversely, when the town's future was again at risk during a labour dispute in 1964, workers reacted with stiff resistance. When the new owner, the Anaconda Company, threatened to close the mine, striking employees mounted a united campaign and called for support from across Canada to keep the mine open. When the dispute was settled seven months later, the union claimed victory over an American corporate giant. This commuter workforce with loose social ties had successfully used notions of local and national community to foster militancy against their employer. The case of Britannia demonstrates how community can both restrain and rouse workers and town residents, shaping their diverse reactions to deindustrialization.